Investigation of Teacher Candidates' Digital Obesity - Ay, Sevinc; Karabatak, Songul; Karabatak, Murat (Institute of Electrical and Electronics Engineers Inc., 2024)
The objective of this study is to investigate the phenomenon of digital obesity among teacher candidates. To achieve this goal, a survey model was employed as a quantitative research method. The participants of this study consisted of 256 teacher candidates who were conveniently sampled from Firat University in Elazi?. To gather relevant information about the teacher candidates, the Digital Obesity Scale was incorporated into the data collection instrument. According to the results obtained from the study, it has been observed that a significant number of teacher candidates use digital devices between 4 and 6 hours per day, and those who use them for more than 7 hours are at a level that needs to be taken into consideration. It has been revealed that teacher candidates mostly use WhatsApp and Instagram. Additionally, it has been revealed that teacher candidates use digital tools mostly for interaction and educational purposes. It has been concluded that the level of digital obesity among teacher candidates is moderate and that gender and the duration of digital device use affect digital obesity to some extent. © 2024 IEEE.
12th International Symposium on Digital Forensics and Security, ISDFS 2024 -- 29 April 2024 through 30 April 2024 -- San Antonio -- 199532
Keywords: digital obesity; digital tools; pre-service teacher